Status Gizi, Tingkat Konsumsi Zat Gizi Besi (Fe) dan Siklus Menstruasi Dengan Kejadian Anemia Remaja Putri : Nutritional Status, Iron (Fe) Consumption Level And Menstrual Cycle With The Incidence Of Anemia Of Adolescent Girls - Putri, Septiara Kharisma; Jeki, Andicha Gustra; Fatmawati, Tina Yuli (Media Publikasi Cendekia Indonesia, 2024)
Background: There are many factors that can cause anemia, including nutritional status, low consumption levels (fe) and abnormal menstrual cycles. Aims: To determine the relationship between nutritional status, levels of consumption of Fe iron nutrients and menstrual cycles with the incidence of anemia in female adolescents at SMPN 18, Merangin Regency. Methods : This type of research is a quantitative study with a cross-sectional design and data collection by means of interviews, checking Hb and distributing questionnaires. The number of samples is 48 teenagers. Data analysis in this study used Univariate and Bivariate analysis using the chi square test to determine the relationship between the dependent variable (Nutritional Status, Consumption Level of iron (fe) nutrients and Menstrual Cycle) with the dependent variable (The incidence of anemia in young women) Results: The results showed that the percentage of under/over nutritional status was 29 respondents (60.4%), the level of iron (fe) consumption was lacking by 35 respondents (72.9%), the menstrual cycle was abnormal by 30 (62.5%). %), the incidence of anemia was 43 (89.6%). There is a relationship between nutritional status and the incidence of anemia (p = 0.041), there is a relationship between the consumption level of iron (fe) and the incidence of anemia (p = 0.006) and there is a relationship between the menstrual cycle and the incidence of anemia (p = 0.022). Conclusion: In this study it can be concluded that the incidence of anemia is quite high in SMPN 18 Merangin District. It is recommended for adolescents to maintain their food intake, because it affects health.